2022
DOI: 10.1038/s41467-022-29363-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain ceramides are cell non-autonomous signals linking lipotoxicity to endoplasmic reticulum stress in skeletal muscle

Abstract: The endoplasmic reticulum (ER) regulates cellular protein and lipid biosynthesis. ER dysfunction leads to protein misfolding and the unfolded protein response (UPR), which limits protein synthesis to prevent cytotoxicity. Chronic ER stress in skeletal muscle is a unifying mechanism linking lipotoxicity to metabolic disease. Unidentified signals from cells undergoing ER stress propagate paracrine and systemic UPR activation. Here, we induce ER stress and lipotoxicity in myotubes. We observe ER stress-inducing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 67 publications
(68 reference statements)
0
32
0
Order By: Relevance
“…In muscle tissues of type 2 diabetic patients, an approximately 20% higher concentration of long-chain ceramides was detected. Animal studies showed that about a 30% lower level of these ceramides in skeletal muscle improved the unfolded protein response [ 47 ]. Liver-specific overexpression of acid ceramidase lowered alcoholic liver steatosis and hepatic insulin resistance, though hepatic ceramide species only modestly declined [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In muscle tissues of type 2 diabetic patients, an approximately 20% higher concentration of long-chain ceramides was detected. Animal studies showed that about a 30% lower level of these ceramides in skeletal muscle improved the unfolded protein response [ 47 ]. Liver-specific overexpression of acid ceramidase lowered alcoholic liver steatosis and hepatic insulin resistance, though hepatic ceramide species only modestly declined [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, elevated ceramide levels appear to worsen leptin resistance, which is important in the pathophysiology of obesity and metabolic syndrome ( Field et al, 2020 ). Secretion of long-chain ceramides C40:1 and C42:1 was also shown to be involved in chronic endoplasmic reticulum stress in skeletal muscle, linking lipotoxicity to metabolic disease ( McNally et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of lipidomics approaches using mass spectrometry, cohort studies have revealed strong correlations between serum and liver ceramides levels and NAFLD pathologies in humans. Aberrant accumulation of ceramide in tissues is thought to be a negative regulator of glucose tolerance and lipid metabolism, which can modulate pathophysiological processes in a variety of diseases including insulin resistance, cardiovascular disease, coronary atherosclerosis, and diabetes [71][72][73][74] (Figure 2, Table 1). Evidence suggests that ceramide contributes to key steps in the onset and progression of NAFLD (Figure 3).…”
Section: Liver Ceramides Contribution To Nafldmentioning
confidence: 99%